- 1-214-256-5804
- info@tutorpace.com

For example, 3ax is a term

In this variable = x

Coefficient of variable = 3a

2x + y = 3 and x – 3y = 12

From the first equation, we can write

y = 3 – 2x

We can substitute this y in the second equation x – 3y = 12

x – 3 (3 – 2x) = 12

x – 9 + 6x = 12

7x – 9 = 12

Now we can add + 9 on both sides

7x – 9 + 9 = 12 + 9

7x = 21

Divide by 7, and then we have

x = 3

Now we can plug this value in y = 3 – 2x = 3 – 2 (3) = 3 – 6 = - 3.

4 (3x + 2) – (x + 5) = - 3

12x + 8 – x – 5 = - 3

11 x = - 6

x = -6/11